ROMANSA TOKOH AKANE DAN TOKOH AOGI DALAM MANGA MOTTO KOKORO NI HOSHI NO KAGAYAKI WO KARYA HIRO MATSUBA - Ari Pebriani, Ni Ketut (Humanis; Volume 15. No.2. Mei 2016)
This study entitled "Romance Figures Akane and Aogi in Manga Motto Kokoro Ni Hoshi No Kagayaki Wo work Matsuba Hiro". The expressions of love and romance characters of Akane and Aogi contained in manga Motto Kokoro Ni Hoshi No Kagayaki Wo is examined. The data source of this research is manga volumes 1-8 Motto Kokoro Ni Hoshi No Kagayaki Wo. The theory used in this research is the theory of sociology of literature proposed by Wellek and Warren (1976) and the theory of love that is by Robert Stemberg (2009). The method used for data analysis in this research is descriptive analysis method. Results from this study indicate that expression of love experienced by Akane and Aogi include (1) Verbal Expression, which is an expression of love and praise, and (2) Nonverbal Expression,action, face expression, and touch. The romance character of Akane and Aogi are (1) Fatuous love (stupid love), and (2) Romantic love (romantic love),
Keywords: expression of love, romance, sociology of literature